Life situation and support during pregnancy among Thai expectant mothers with depressive symptoms and their partners: a qualitative study - Nitikorn Phoosuwan; Pornpun Manasatchakun; Leif Eriksson; Pranee C. Lundberg (BMC, 2020)
Abstract Background Expectant parents may have positive and negative emotions during pregnancy and receive support from different sources. Studies on life situation and support among couples have rarely been conducted. This study aims to explore life situation and support during pregnancy among expectant mothers with depressive symptoms and their partners. Methods Twenty-seven expectant mothers, in the last trimester of pregnancy with depressive symptoms (Edinburgh Postnatal Depression Scale score ≥ 7) from seven public antenatal care clinics in Sakonnakhon, a north-eastern province of Thailand, and their partners were interviewed. In total, 54 semi-structured interviews were subjected to content analysis. Results Four categories emerged: (1) Having obstacles in life, (2) Facing life transition, (3) Enhancing confidence, and (4) Dissatisfaction with support. The informants described obstacles regarding economy, fear of health problems, getting an abnormal child and partners' behaviours. They received support from family members and social networks, but some were dissatisfied with the support from the healthcare. For example, expectant fathers wished to receive more health information and be more involved. Conclusions Healthcare professionals should be aware of the influence of cultural and contextual factors when providing antenatal care to expectant parents. Male involvement in the care must not be neglected.